An Overview of Systematic Reviews of Chinese Herbal Medicine in the Treatment of Migraines - Fu, Guojing; Fan, Xueming; Liang, Xiao; Wei, Jingjing; Jia, Min; Liu, Shaojiao; Shen, Wei; Zhang, Yunling (Frontiers in Pharmacology, 2022)
Background: In the past, studies based on systematic reviews (SRs) or meta-analyses (MAs) have been used to assess the efficacy of Chinese herbal medicine (CHM) in the therapy of migraines. However, robust conclusions have not yet been determined because of variation in methodological and evidence quality of these SRs/MAs. Objectives: We aimed to evaluate the methodological and reporting quality of SRs/MAs and evaluate the available evidence of the efficacy of CHM treatment of migraines. Methods: We searched eight electronic databases from inception until January 10, 2022, without language restrictions. Two researchers were independently responsible for study screening and data extraction. The methodological and reporting quality of SRs/MAs were assessed using A Measurement Tool to Assess Systematic Reviews (AMSTAR) 2 and Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA). The evidence quality of included SRs/MAs was evaluated by Grading of Recommendations Assessment, Development and Evaluation (GRADE). In addition, a descriptive analysis of the included SRs/MAs was included. Results: Sixteen SRs/MAs, including 69 outcomes, were finally included in this overview. The data synthesis of the included SRs/MAs outcomes showed that CHM plus Western medicines (WM) was beneficial in the improvement of migraines. In comparison, there was conflicting evidence for the effectiveness of CHM used alone. CHM was better than WM in improving responder rate and acute medication usage, and was superior to a placebo in improving migraine days, responder rate, and migraine duration. However, there was insufficient evidence to verify the effectiveness of CHM for migraine treatment regarding pain severity and migraine frequency. All the included SRs/MAs showed extremely low methodological and reporting quality. The results of the GRADE system indicated that the quality of most of the pooled evidence was very low. The GRADE methodology revealed that the most pooled evidence had very low quality. Conclusions: CHM may be beneficial in improving migraines and can be used as a complementary therapy. However, we should treat the conclusions cautiously because of the inferior quality of evidence. Future SRs/MAs should focus on improving methodological and reporting quality. High-quality RCTs are needed to provide strong evidence for the CHM treatment of migraines.